Motyw Dnia Pańskiego w Księdze Sofoniasza na tle mesjańskiej radości w So 3,14-17 - Zawadzki, Arnold (Collectanea Theologica, 2018)
The article seeks to highlight the problem of the theological complexity of the Book of Zephaniah, that would be intriguing to the general reader, and in which the categorical divine oracle of judgment collides with a strong invitation to the messianic joy (Ze. 3:14-17). By starting from the border verse (Ze. 3:9), where the oracle of judgment rapidly turns into an oracle of salvation, the author tries to examine the internal dynamics of this theological turning point. The main purpose of this analysis is to attempt to understand the nature of the day of the Lord which, in the book of Zephaniah, turns out to be at the same time the day of judgment and the day of salvation. Based on the classic Aristotelian doctrine of the four causes, the author puts in order disparate material on the day of the Lord in the book of Zephaniah and sees in it a number of references to the Jahwistic version of the account of the sin concerning the sons of God (Gn. 6:1-4) and the flood (Gn. 6:5-8,22; 9.1-17). The article may become a contribution to the understanding of the impact of the Pentateuchal sources on the prophetic tradition.